Investment Decision of PTKIN Academic Community in Central Java and Yogyakarta in the Online Trading System - Pertiwi, Imanda Firmantyas Putri; Kasdi, Abdurrohman (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2020)
This research aims to predict the effect of financial literacy, ease of entry into the capital market and the role of university to academic community’s investment decisions on the online trading system. This empirical research was carried out by taking academic community of State Islamic University (PTKIN) in Central Java and Yogyakarta as the subjects of the research. The novelty of this research is the formulation of indicators of ease of entry to the capital market and the role of university, which are formulated through not only literature review, but also field observations. Using Partial Least Square (PLS) as the analysis tools, this research finds that financial literacy and ease of entry are being able to predict the influence the academic community's investment decisions. Role of universities variable, although it is empirically proven that four PTKIN samples have been maximized, can not been able to influence the investment decisions of the academic community.